The Contribution of Prosperity Gospel to the Rise of Pentecostalism in Mansa Township, Zambia - Hachintu, Joseph K.; Mulonga, Mellanie (International Journal of Humanities, Social Sciences and Education, 2023)
The purpose of this article was to explore the prosperity gospel and its contribution to the rapid rise of Pentecostalism in Mansa Township of Luapula Province in Zambia. The study was deemed important in the sense that it would contribute towards the current debates on the prosperity gospel and how it has contributed to the rapid rise of Pentecostalism in other parts of the country other than the area under study. It was also believed that the study would add to the body of knowledge and literature on the influence of the prosperity gospel. Theoretically premised on Marx Weber's (1930) essay “The Protestant Ethic and the Spirit of Capitalism”, focusing on Calvin's doctrine, the study drew upon the data obtained through qualitative research strategy from 25 respondents. One-on-one interviews and Focus Group Discussions were conducted with experienced clergymen, the youth, laymen and women from Neo-Pentecostal churches and NonPentecostal churches. Data were analysed qualitatively using thematic analysis techniques. The findings of the study were that the rapid rise of Pentecostalism in Mansa Township was a result of some social, economic, spiritual and health factors which included illnesses, bareness, poverty, unemployment, misfortunes, and marital issues that people underwent. It was also discovered in the study that, the prosperity gospel possessed some aspects that made people get attracted to churches that propagated the gospel. Some of such aspects included extensive motivation, providing quick solutions to people's problems, the attractiveness of the gospel, and building competition, to mention but a few.
free